2006
DOI: 10.2323/jgam.52.37
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationship within the Erythrobasidium clade: Molecular phylogenies, secondary structure, and intron positions inferred from partial sequences of ribosomal RNA and elongation factor-1α genes

Abstract: Extensive investigations of molecular systematics in the basidiomycetous yeasts using the sequences of 26S rDNA (Fell et al., 2000) and internal transcribed spacers (ITSs) (Scorzetti et al., 2002) established that these molecular data are useful tools for the delineation of species. However, the phylogenetic relationships among some taxa derived from the analysis of 26S rDNA sequences were not always identical to those based on the ITS regions. In addition, many branches of the 26S rDNA-based tree were not con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…This clade was consistently resolved and strongly supported in all the trees constructed in this ( Table 3 , Fig. 6 ) and previous studies ( Nagahama et al., 2006 , Boekhout et al., 2011 ). The genus Sakaguchia was treated as ‘ incertae sedis ’ in Aime et al., 2006 , Bauer et al., 2006 and Boekhout et al.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This clade was consistently resolved and strongly supported in all the trees constructed in this ( Table 3 , Fig. 6 ) and previous studies ( Nagahama et al., 2006 , Boekhout et al., 2011 ). The genus Sakaguchia was treated as ‘ incertae sedis ’ in Aime et al., 2006 , Bauer et al., 2006 and Boekhout et al.…”
Section: Resultssupporting
confidence: 82%
“…5 , Fig. 6 ), being in agreement with Nagahama et al., 2006 , Boekhout et al., 2011 and Yurkov et al. (2015) .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Rhodotorula mucilaginosa CBS 316 T was included to root the tree. In clade A, the subgroups defined by Nagahama et al (2006) as well as our newly described seventh subgroup (Magnisporus) are indicated. Bootstrap percentages (from 1000 replicates) ≥50 % are shown.…”
mentioning
confidence: 99%
“…Nagahama et al (2006) defined six robust subgroups within the Erythrobasidium clade (Erythrobasidiales). However, they did not include S. magnisporus in their study.…”
mentioning
confidence: 99%